STRATEGI KOMUNIKASI PEMASARAN STREET FOOD DI JALAN LENGKONG KECIL KOTA BANDUNG DALAM MENARIK PERHATIAN PENGUNJUNG - Hasya Nindi Fadillah; Feni Desvianda; M. Afrizal Maulana (Jurnal Manajemen Kompeten, 2022)
Street food sells food and beverages, prepares and serves them on the roadside or other public places for immediate or short-term consumption. Street food helps develop small businesses with very low capital investment. Many street foods are found in Bandung, but only a few are known by the public, this is due to a lack of communication. This research aimed to explore the marketing communication strategy of street food in Jalan Lengkong Kecil, Bandung City. The research used a qualitative-descriptive approach. The research subjects were street food vendors on Jalan Lengkong Kecil, Bandung City. The research was conducted from September 2022 to December 2022. Data collection techniques were carried out through interviews with several street food traders and administrators of Jalan Lengkong Kecil Bandung City, to explore information about 1) History, 2) Condition, and 3) Strategy. The results of the study found that street food traders and visitors on Jalan Lengkong Kecil Bandung City worked together to promote the street food, so that it can be better known by the public, such as by promoting on social media, recommending to friends, and making innovations so that the street food remains crowded with visitors. These findings showed that the marketing communication strategy in street food on Jalan Lengkong Kecil, Bandung City had been carried out well.